Effect of ursodeoxycholic acid on methionine adenosyltransferase activity and hepatic glutathione metabolism in rats. Issue 5 (1st May 2002) - Rodríguez-Ortigosa, C M; Cincu, R N; Sanz, S; Ruiz, F; Quiroga, J; Prieto, J
Abstract : Background and aims: Both bile salts and glutathione participate in the generation of canalicular bile flow. In this work, we have investigated the effect of different bile salts on hepatic glutathione metabolism. Methods: Using the isolated and perfused rat liver, we studied hepatic glutathione content, and metabolism and catabolism of this compound in livers perfused with taurocholate, ursodeoxycholate, or deoxycholate. Results: We found that in livers perfused with ursodeoxycholate, levels of glutathione and the activity of methionine adenosyltransferase (an enzyme involved in glutathione biosynthesis) were significantly higher than in livers perfused with other bile salts. In ursodeoxycholate perfused livers, methionine adenosyltransferase showed a predominant tetrameric conformation which is the isoform with highest activity at physiological concentrations of substrate. In contrast, the dimeric form prevailed in livers perfused with taurocholate or deoxycholate. The hepatic activities of γ-glutamylcysteine synthetase and γ-glutamyltranspeptidase, enzymes involved, respectively, in biosynthetic and catabolic pathways of glutathione, were not modified by bile salts. Conclusions: Ursodeoxycholate specifically enhanced methionine adenosyltransferase activity and hepatic glutathione levels. As glutathione is a defensive substance against oxidative cell damage, our observations provide an additional explanation for the known hepatoprotective effects of ursodeoxycholate.